Numeric Rating Scales Show Prolonged Post-exertional Symptoms After Orthostatic Testing of Adults With Myalgic Encephalomyelitis/Chronic Fatigue Syndrome - van Campen, C (Linda) M. C.; Rowe, Peter C.; Verheugt, Freek W. A.; Visser, Frans C. (Frontiers in Medicine, 2021)
Introduction: Muscle pain, fatigue, and concentration problems are common among individuals with myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). These symptoms are commonly increased as part of the phenomenon of post-exertional malaise (PEM). An increase in the severity of these symptoms has been described following physical or mental exercise in ME/CFS patients. Another important symptom of ME/CFS is orthostatic intolerance, which can be detected by head-up tilt testing (HUT). The effect of HUT on PEM has not been studied extensively. For this purpose we assessed numeric rating scales (NRS) for pain, fatigue, and concentration pre- and post-HUT. As pain is a core symptom in fibromyalgia (FM), we sub-grouped ME/CFS patients by the presence or absence of FM. Methods and results: In eligible ME/CFS patients who underwent HUT, NRS of pain, fatigue, and concentration were obtained pre-HUT, immediately after HUT, at 24 and 48 hours, and at 7 days post-test. We studied 174 ME/CFS patients with FM, 104 without FM, and 30 healthy controls (HC). Values for all symptoms were unchanged for HC pre- and post-HUT. Compared to pre-HUT, the 3 NRS post-HUT were significantly elevated in both ME/CFS patient groups, even after 7 days. NRS pain was significantly higher at all time-points measured in the ME/CFS patients with FM compared to those without FM. In ME/CFS patients, the maximum fatigue and concentration scores occurred directly post-HUT, whereas pain perception reached the maximum 24 hours post-HUT. Conclusion: Numeric rating scale scores of pain, fatigue, and concentration were significantly increased, even at seven days post-HUT compared to pre-HUT in ME/CFS patients with and without FM, suggesting that orthostatic stress is an important determinant of PEM.